Detecting Ads in Video Streams Using Acoustic and Visual Cues. - Covell, Michele; Baluja, Shumeet; Fink, Michael (Computer (00189162), 2006)
The article provides information on various techniques developed by researchers that detect and remove advertisements in video streams in the U.S. One is the repetition-based approach developed by John M. Gauch and Abhishek Shivadas. The percentage of repeated advertisements in repetition-based approach grows with the size of the video collection. In line with this work, a technique that use acoustic as well as visual cues to find efficiently and segment repeated material within a large collection of monitored video streams is developed.